2024
DOI: 10.1039/d4fo00941j
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance, combined with health-related lifestyles, psychological traits and adverse cardiometabolic profiles, is associated with cardiovascular diseases: findings from the BHMC study

Tao Yin,
Shuo Chen,
Yingying Zhu
et al.

Abstract: The triglyceride glucose (TyG) index is a reliable marker of insulin resistance, however, its combined impact with modifiable lifestyle risk factors and psychological traits on cardiovascular diseases (CVDs) remains unclear.The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…As mentioned earlier, since the TyG index primarily reflects the level of IR in the body, and IR is closely associated not only with the onset of type 2 diabetes mellitus but also with cardiovascular disease risk factors such as hyperlipidemia, hypertension, or coagulation abnormalities. 25,26 Currently, the TyG index has been confirmed to be closely associated with the prognosis of healthy individuals or patients with coronary heart disease. Yang et al studied 592,616 individuals and found an association between the TyG index and ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, since the TyG index primarily reflects the level of IR in the body, and IR is closely associated not only with the onset of type 2 diabetes mellitus but also with cardiovascular disease risk factors such as hyperlipidemia, hypertension, or coagulation abnormalities. 25,26 Currently, the TyG index has been confirmed to be closely associated with the prognosis of healthy individuals or patients with coronary heart disease. Yang et al studied 592,616 individuals and found an association between the TyG index and ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that several factors can influence the levels of FPG, including obesity 5 , hypertension 6 , an unhealthy life style 7 , and dysimmunity 8 . The immune system, comprising both the innate and adaptive components, has been unequivocally linked to metabolic syndrome 9 .…”
Section: Introductionmentioning
confidence: 99%